miR-142-3p Contributes to Early Cardiac Fate Decision of Embryonic Stem Cells - Zhong-Yan Chen; Fei Chen; Nan Cao; Zhi-Wen Zhou; Huang-Tian Yang (Stem Cells International)
MicroRNAs (miRNAs) play important roles in cell fate decisions. However, the miRNAs and their targets involved in the regulation of cardiac lineage specification are largely unexplored. Here, we report novel functions of miR-142-3p in the regulation of cardiomyocyte differentiation from mouse embryonic stem cells (mESCs). With a miRNA array screen, we identified a number of miRNAs significantly changed during mESC differentiation into the mesodermal and cardiac progenitor cells, and miR-142-3p was one among the markedly downregulated miRNAs. Ectopic expression and inhibition of miR-142-3p did not alter the characteristics of undifferentiated ESCs, whereas ectopic expression of miR-142-3p impaired cardiomyocyte formation. In addition, ectopic expression of miR-142-3p inhibited the expression of a cardiac mesodermal marker gene Mesp1 and downstream cardiac transcription factors Nkx2.5, Tbx5, and Mef2c but not the expression of three germ layer-specific genes. We further demonstrated that miR-142-3p targeted the 3′-untranslated region of Mef2c. These results reveal miR-142-3p as an important regulator of early cardiomyocyte differentiation. Our findings provide new knowledge for further understanding of roles and mechanisms of miRNAs as critical regulators of cardiomyocyte differentiation.